Efficacy and Safety of Lidocam Topical Gel (4% Lidocaine—0.3% Meloxicam) for Pain and Inflammation Management during Castration and Tail Docking in Piglets - Denis Nagel; Brenda Ralston; Andrea Hanson; Les Burwash; Heather Matheson-Bird; Barbara Olson; Crystal Schatz; Merle Olson (Animals, 2024)
(1) Background: It has been well established that castration and tail docking are both painful during and following the procedure, yet there are limited convenient and effective products to address both short-term and long-term pain. Lidocam Topical Gel (LTG) (4% lidocaine and 0.3% meloxicam) was developed to address industry needs for an effective and safe product to address animal welfare concerns regarding castration and tail docking in piglets. (2) Methods: Study 1: Male piglets aged 4–8 days of age were treated with LTG (n = 30) or a control gel (n = 30). Approximately 30 min after application of the gel, the piglets were surgically castrated and tail docked. The efficacy of pain control during the surgical procedures and post-procedure (24 h) pain and inflammation control were evaluated using both behavioral and physiological measurements. Study 2: Meloxicam residue depletion following LTG treatment was followed for 28 days. Study 3: Clinical and pathological safety were evaluated in five groups of eight piglets receiving LTG with: (1) no treatment, (2) nominal topical dose, (3) two times the nominal topical dose, (4) three times the nominal topical dose, and 5) one times the nominal topical dose and 2 mL of LTG by oral gavage daily for 3 days. (3) Results: LTG-treated piglets had a significant reduction in electrocutaneous stimulation response before the procedures and 4 and 24 h post-procedures. Stress vocalization intensity and duration were less in piglets receiving LTG during the surgical procedures. Plasma cortisol and substance P were significantly lower in LTG-treated piglets 3 h after castration and tail docking. The weight and average daily gain were significantly increased in piglets receiving LTG. LTG did not interfere with wound healing or cause irritation at the application sites. There were no abnormal clinical or pathological findings associated with the use of LTG at three times the nominal dose given daily for three days. As meloxicam persisted in the application site tissue, a slaughter withdrawal time of 24 days was determined. (4) Conclusions: When applied to the skin 30 min before castration and tail docking, LTG is effective in surgical pain control and provides post-surgical pain control for up to 24 h. LTG is safe for use in piglets and provides an acceptable withdrawal time for commercial use. LTG is a potentially effective product for commercial use for piglet castration and tail docking.